Estimation of counterweight for shaking force balancing of a crank-rocker mechanism - Mohammed, S.E. (Trans Tech Publications Ltd, 2014)
This paper proposes a method of balancing the shaking force of a crank-rocker mechanism which rotates at a constant angular speed with zero-unbalanced angle. In this approach, the kinematic synthesis and dynamic behavior of the mechanism are combined. The method is realized by modeling the mass of the connecting rod to represent two concentrated masses placed at the crank and rocker pins. The shaking forces balancing are done by adding counterweight masses to the crank and the rocker. The verification and numerical computation of the proposed balancing technique were carried out using ADAMS Software. The results showed that the sum of all the resultant forces was completely eliminated for the newly-balanced crank rocker mechanism. Â© (2014) Trans Tech Publications, Switzerland.